Chitosan/PLGA particles for controlled release of α-tocopherol in the GI tract via oral administration. (November 2011) - Murugeshu, Abitha; Astete, Carlos; Leonardi, Claudia; Morgan, Timothy; Sabliov, Cristina M
Aim: The physiochemical properties, controlled release characteristics, stability and cellular uptake of chitosan (Chi)/poly(D, L -lactide-co-glycolide) (PGLA) and PLGA particles with entrapped α-tocopherol were investigated to understand the behavior of these nanoparticles in the GI tract.Materials & Methods: Chi/PLGA and PLGA particles stabilized by lecithin were synthesized and fully characterized for oral gastrointestinal delivery via transmission electron microscopy, dynamic light scattering, high-performance liquid chromatography and fluorescence microscopy.Results: Particle stability was pH- and system-dependent. In vitro release profiles showed a higher percentage of drug released in the intestinal domain by Chi/PLGA as opposed to the PLGA nanoparticles. Fluorescent counterparts of these particles were confirmed to associate with the surface of the intestinal villi, and penetrate deep in the endothelial lining of rabbit intestinal explants, indicating uptake.Conclusion: In vitro and ex vivo results showed that PLGA and Chi/PLGA nanoparticles were efficiently taken up by the GI tract and could be optimized to deliver αtocopherol to the intestine and improve its bioavailability.